Pola Angin Laut di Kawasan Pantai TPI Desa Bulurejo Kabupaten Lumajang dengan Metode Windrose - George Winaktu; Ita Suhermin Ingsih (Fakultas Teknik, 2022)
Sea breezes or what are commonly referred to as monsoon winds have varying speeds, as well as different directions at each location. This study discusses the wind speed that occurs on the coast of Java Island, especially at TPI Beach, Lumajang Regency. Where this wind is a variable that has a certain speed. This wind speed is indicated to also cause changes in the shoreline where the wind, which can cause waves, hits the shore repeatedly so that it experiences abrasion. The wind data used is wind data for 5 years, from 2015 to 2020 obtained from meteorological reanalysis data for the study of wind energy potential ECWMF (European Center for Medium-Range Weather Forecasts). At this TPI beach location, the average wind speed ranges from 7-11 knots or 3-5 m/s, where the direction of arrival after data processing with the Windrose method is obtained, and east is the dominant wind comes from. In addition to the wind speed that occurred at TPI Beach, it was also discussed about the wind speed that occurred at other locations, some of which also experienced changes in the shoreline, and several other locations that did not experience the same thing but were located along the coast of Java Island both from West Java and Central Java.